Chapter 5.21 Research Management and Administration in Cyprus - Andri Charalambous; Pierantonios Papazoglou (Emerald Publishing Limited, 2023)
Research managers and administrators (RMAs) should not be forgotten as part of the professional workforce populating today's research ecosystems of universities or research institutes, with interactions and contributions that matter ( Poli, 2018a ). Unfortunately, since they are still often regarded as employees who are neither senior management nor researchers, their role still suffers vagueness and ambiguity ( Allen-Collinson, 2009 ). Consequently, RMAs are still unrecognised and unacknowledged, and often misunderstood as support staff or bureaucrats ( Rhoades, 2010 ). This country-specific case study of Cyprus introduces the readers to the Cypriot research ecosystem, so as to contextualise the landscape within which the Cypriot RMAs operate professionally. After briefly discussing the evolution of the RMA profession in Cyprus and glimpsing at what might be the current Cypriot RMA community, the chapter elaborates on RMA demographics derived from the `RMA in Cyprus Questionnaire', which was formulated based on the RAAAP-3 survey. At its closure, the chapter proposes the establishment of the `CyARMA – Cyprus Association of Research Managers and Administrators', as the body to advocate the standardisation, professionalisation and, more importantly, the recognition of the RMA profession in Cyprus.
10.1108/978-1-80382-701-820231055; 10.1108/978-1-80382-701-820231055; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262